2020
DOI: 10.1101/2020.09.04.280081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monoclonal Antibodies Capable of Binding SARS-CoV-2 Spike Protein Receptor Binding Motif Specifically Prevent GM-CSF Induction

Abstract: A severe acute respiratory syndrome (SARS)-like coronavirus (SARS-CoV-2) has recently caused a pandemic COVID-19 disease that infected more than 25.6 million and killed 852,000 people worldwide. Like the SARS-CoV, SARS-CoV-2 also employs a receptor-binding motif (RBM) of its envelope spike protein for binding the host angiotensin-converting enzyme 2 (ACE2) to gain viral entry. Currently, extensive efforts are being made to produce vaccines against a surface fragment of a SARS-CoV-2, such as the spike protein, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It was further noted that the amino acid sequence similarities between SARS-CoV-2 and cellular proteins including Mitochondrial M2, F-actin and TPO were the source of reactivities. Recently, Qiang et al (2021) showed high homology between a segment (YNYLYR) in RBM and the epitope sequence NDALYEYLRQ of several monoclonal antibodies against tetranectin. The two tetranectin monoclonal antibodies were shown to bind RBM with a KD of 17.4 and 62.8 nM, respectively [57].…”
Section: Presence Of Antibodies Against S Protein In Individuals Without Sars-cov-2 Infection: Results Of Potential Molecular Mimicrymentioning
confidence: 99%
“…It was further noted that the amino acid sequence similarities between SARS-CoV-2 and cellular proteins including Mitochondrial M2, F-actin and TPO were the source of reactivities. Recently, Qiang et al (2021) showed high homology between a segment (YNYLYR) in RBM and the epitope sequence NDALYEYLRQ of several monoclonal antibodies against tetranectin. The two tetranectin monoclonal antibodies were shown to bind RBM with a KD of 17.4 and 62.8 nM, respectively [57].…”
Section: Presence Of Antibodies Against S Protein In Individuals Without Sars-cov-2 Infection: Results Of Potential Molecular Mimicrymentioning
confidence: 99%